DEVELOPMENT OF THE ALIBABA MEDIA GAME ASSISTED WITH THE MAKE A MATCH MODEL IN ARABIC LANGUAGE LEARNING TO IMPROVE THE VOCABULARY MASTERY OF CLASS IV PRIMARY SCHOOL STUDENTS - Faizah, Faizah; Khurotul A’yuni; M. Fadloli Al-Hakim (Al-Mudarris: Journal Of Education, 2024)
This study aims to determine the development of alibaba game media assisted by make a match model in Arabic language learning to improve vocabulary mastery of fourth grade students at MI Salafiyah Kranggan. The research method used is research & development (RnD) with a mix method research approach. This research uses the ADDIE from Dick & Carey development model with a sample of class IV A and IV B students totaling 49 students and 9 teachers. The results showed success in vocabulary mastery using alibaba game media.  The alibaba game learning media assisted by make a match model also provides interactive quizzes and interesting games. The use of alibaba game learning media also has disadvantages from the aspect of its need for smartphones, and the production procedure requires video editing. Therefore, teachers are advised to improve their skills in using digital technology and interesting interactive learning.